On the energy scaling behaviour of a singularly perturbed tartar square - Rüland, Angkana; Tribuzio, Antonio (Arxiv, 2021)
In this article we derive an (almost) optimal scaling law for a singular perturbation problem associated with the Tartar square. As in [Win97, Chi99], our upper bound quantiﬁes the well-known construction which is used in the literature to prove ﬂexibility of the Tartar square in the sense of ﬂexibility of approximate solutions to the diﬀerential inclusion. The main novelty of our article is the derivation of an (up to logarithmic powers matching) ansatz free lower bound which relies on a bootstrap argument in Fourier space and is related to a quantiﬁcation of the interaction of a nonlinearity and a negative Sobolev space in the form of “a chain rule in a negative Sobolev space”. Both the lower and the upper bound arguments give evidence of the involved “inﬁnite order of lamination”.